Redefining the Therapeutic Ladder in Refractory Chronic Constipation: A Systematic Review and Meta-Analysis of the Role of Ileal Bile Acid Transporter (IBAT) Inhibitors - Imam Suprianto; Fania Rizkyani Sariza (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Chronic constipation (CC) refractory to conventional laxatives is a prevalent clinical challenge that significantly impairs quality of life. Ileal bile acid transporter (IBAT) inhibitors, a novel class of drugs, modulate colonic function by increasing the delivery of bile acids to the colon. This study aimed to quantitatively synthesize the evidence for the efficacy and safety of IBAT inhibitors in this difficult-to-treat population to clarify their position in the therapeutic algorithm. Methods: Following PRISMA guidelines, we systematically searched PubMed, Scopus, Embase, and Cochrane CENTRAL, along with clinical trial registries, from inception to June 1st, 2025. We included parallel-group, randomized controlled trials (RCTs) comparing the IBAT inhibitor elobixibat with placebo in adults with CC refractory to at least two prior laxative classes. The primary efficacy outcome was the overall responder rate. Key secondary outcomes included change in spontaneous bowel movements (SBMs) per week, quality of life (QoL) scores, and incidence of adverse events. Data were pooled using a random-effects model. Number needed to treat (NNT) and to harm (NNH) were calculated. Results: Our search identified six eligible RCTs enrolling 2,155 patients. Patients treated with elobixibat were significantly more likely to be responders compared to placebo (Risk Ratio [RR] = 2.58; 95% CI: 1.87–3.56; p < 0.00001), with moderate heterogeneity (I² = 59%). The NNT to achieve one additional responder was 5 (95% CI: 4–7). Elobixibat significantly increased the mean number of SBMs per week (Mean Difference [MD] = 1.65; 95% CI: 1.19–2.11; p < 0.00001; I² = 64%). The most common adverse events were gastrointestinal; elobixibat significantly increased the risk of diarrhea (RR = 4.21; 95% CI: 3.01–5.89; NNH = 6) and abdominal pain (RR = 2.35; 95% CI: 1.63–3.38; NNH = 11). Most events were mild to moderate. Conclusion: This meta-analysis provides robust evidence that the IBAT inhibitor elobixibat is a highly effective therapy for refractory CC, offering a significant improvement in symptoms for a substantial portion of patients. This benefit must be carefully balanced against the high incidence of mechanism-based gastrointestinal side effects. These findings establish elobixibat as a potent, mechanistically distinct option, thereby informing its strategic placement on the therapeutic ladder for patients failed by conventional laxatives.